Starotestamentalne cytaty i aluzje w ewangelicznych opisach męki i śmierci Jezusa - Homerski, Józef (The Biblical Annals, 2017)
The author starts with an analysis of the New Testament texts containing quotations from the Old Testament. Then he examines the contents and context of the quoted line in its original place, and on the basis of these two analyses he examines the influence of the Old Testament on the description in the Gospel. He infers that the Evangelists have used the quotations and allusions from the Old Testament in relation to secondary details of the Passion of Christ. So important Old Testament texts as Isa. 52,13-53,12 have not been quoted probably in order not to give the faithful the impression that undertaking this passion and death for human sins, Jesus just fulfilled the prophecies. The task of redemption through Christ’s Passion and Death was an expression of so great a love towards the Heavenly Father, and through him to the people, and was so fruitful, that no prophecy of the Old Testament could fully reflect this reality.